2018
DOI: 10.1016/j.cct.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Positive reinforcement targeting abstinence in substance misuse (PRAISe): Study protocol for a Cluster RCT & process evaluation of contingency management

Abstract: There are approximately 256,000 heroin and other opiate users in England of whom 155,000 are in treatment for heroin (or opiate) addiction. The majority of people in treatment receive opiate substitution treatment (OST) (methadone and buprenorphine). However, OST suffers from high attrition and persistent heroin use even whilst in treatment. Contingency management (CM) is a psychological intervention based on the principles of operant conditioning. It is delivered as an adjunct to existing evidence based treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Each cluster was randomly assigned to additionally provide either: i) positive reinforcement in the form of a £10 voucher given to participants at each weekly appointment for both on-time attendance and abstinence from opiates using an instant cup test (CM Abstinence group); ii) positive reinforcement in the form of a £10 voucher given at each weekly appointment for on-time attendance only (CM Attendance group); or no CM. The main clinical results (9) and design details (10) are reported elsewhere.…”
Section: Interventionsmentioning
confidence: 99%
“…Each cluster was randomly assigned to additionally provide either: i) positive reinforcement in the form of a £10 voucher given to participants at each weekly appointment for both on-time attendance and abstinence from opiates using an instant cup test (CM Abstinence group); ii) positive reinforcement in the form of a £10 voucher given at each weekly appointment for on-time attendance only (CM Attendance group); or no CM. The main clinical results (9) and design details (10) are reported elsewhere.…”
Section: Interventionsmentioning
confidence: 99%
“…Metrebian et al [10]. conducted research in the UK and suggested that CM intervention should be included in the drug treatments in the UK.…”
Section: Contingency Management In Quitting Drug Abusementioning
confidence: 99%
“…We employed a pragmatic cluster randomised controlled trial design described elsewhere. 18 The unit of randomisation was the drug clinic (cluster) rather than individual participant. This was for three reasons: (1) to reduce the likelihood of contamination if staff were delivering and patients receiving different interventions at the same drug clinic; (2) to reduce interpatient contamination as patients themselves constitute a local social network; and (3) to reduce the risk of low recruitment, poor compliance and high dropout within treatment as usual (TAU) arm if participants receiving TAU were denied an incentive offered to others in the same clinic.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…More detail is provided in the protocol. 18 Lussier et al 8 estimated a mean weighted effect size of 0.39 from three studies with an opiate use outcome measure (CM vs control). For a two-sided test, alpha=0.05, 5% attrition, 80% power to detect an effect size of 0.39, 111 participants per group were required.…”
Section: Sample Size Calculationmentioning
confidence: 99%